Human Ubiquitin-Specific Peptidase 18 Is Regulated by microRNAs via the 3'Untranslated Region, A Sequence Duplicated in Long Intergenic Non-coding RNA Genes Residing in chr22q11.21 - Rubino, Erminia; Cruciani, Melania; Tchitchek, Nicolas; Le Tortorec, Anna; Rolland, Antoine D.; Veli, Önay; Vallet, Leslie; Gaggi, Giulia; Michel, Frédérique; Dejucq-Rainsford, Nathalie; Pellegrini, Sandra (Frontiers in Genetics, 2021)
Ubiquitin-specific peptidase 18 (USP18) acts as gatekeeper of type I interferon (IFN) responses by binding to the IFN receptor subunit IFNAR2 and preventing activation of the downstream JAK/STAT pathway. In any given cell type, the level of USP18 is a key determinant of the output of interferon- stimulated transcripts. How the baseline level of USP18 is finely tuned in different cell types remains ill defined. Here we identified miRNAs that efficiently target USP18 through binding to the 3’UTR. Among these, three miRNAs are particularly enriched in circulating monocytes which exhibit low baseline USP18. Intriguingly, the USP18 3’UTR sequence is duplicated in human and chimpanzee genomes. In humans, we found several copies of the 3’UTR that are embedded in long intergenic non-coding (linc) RNA genes residing in chr22q11.21 and exhibiting a tissue-specific expression pattern. Interestingly, one of these lincRNAs (here linc-UR-B1) is uniquely and highly expressed in testis. RNA-seq data analyses from testicular cell subsets revealed a positive correlation between linc-UR-B1 and USP18 expression in spermatocytes and spermatids. Overall, our findings uncover a set of miRNAs and lincRNAs, which may be part of a network evolved to fine-tune baseline USP18, particularly in cell types where IFN responsiveness needs to be tightly controlled.